Effects of Short-Term Cell Phone Exposure on Eeg, Ecg And Blood Pressure in Males And Females of Human - Khalid, Habiba Siamand; Rasul, Bizhar Ramadhan; Maulood, Ismail Mustafa (Science Journal of University of Zakho, 2013)
Mobile phones have become important devices of modern communication. As a result of the widespread increase in use of this technology, concerns have been raised regarding the potential impact on human health, particularly on the CNS. The aim of the present study is to investigate the effect of cell phone on EEG, ECG, blood pressure and in both sexes of human. Thirty two volunteers (16 males, 16 females) who had participated in the original study. During mobile exposure for a period of 30 minutes , EEG, ECG and some hemodynamic were measured . The mobile phone which used in the study was a Nokia model .Statistical analysis revealed that alpha and beta amplitude during closed eye were increased after cell phone exposure for 30 minutes. Alpha amplitude was also significantly elevated during opened eye. The result of present study shown that cell phone exposure for (30)minutes didn’t statistically change hemodynamic parameters ,however diastolic blood presser (DBP)and heart rate were slightly increased . ECG waves and amplitude are also not changed with exception of QT inter vale. In conclusion, the results suggested that cell phone exposure for 30 minutes affect alpha amplitude rather than beta amplitude values especially during closed eye. These changes of alpha waves represents the change in parieto-occiptal region of the brain.